Persistent Cushing’s Disease after Transsphenoidal Surgery: Challenges and Solutions - Albani, Adriana; Theodoropoulou, Marily (Experimental and Clinical Endocrinology & Diabetes, 2020)
Transsphenoidal surgery remains the primary treatment for Cushing’s disease (CD). However, despite the vast improvements in pituitary surgery, successful treatment of CD remains a great challenge. Although selective transsphenoidal removal of the pituitary tumor is a safe and effective procedure, the disease persists in around 22% of CD patients due to incomplete tumor resection. The persistence of hypercortisolism after pituitary surgery may also be the consequence of a misdiagnosis, as can occur in case of ectopic ACTH secretion or pseudo-Cushing. Considering the elevated mortality and morbidity characterizing the disease, a multidisciplinary approach is needed to minimize potential pitfalls occurring during the diagnosis, avoid surgical failure and provide the best care in those patients who have undergone unsuccessful surgery. In this review, we analyze the factors that could predict remission or persistence of CD after pituitary surgery and revise the therapeutic options in case of surgical failure.
Keywords: Cushing’s disease; corticotroph tumor; persistence; remission; steroidogenesis inhibitors; pasireotide